Enhancing Problem-Solving in Junior High School Mathematics and Science Through Guided Inquiry and Deeper Learning: A Systematic Literature Review - Arif Desramaza; Elita Zusti Jamaan; Yerizon; Ahmad Fauzan (Postgraduate, University of Mataram, 2026)
This systematic literature review examines the integration of Guided Inquiry and Deeper Learning models to enhance problem-solving skills in junior high school Mathematics and Science education. Following PRISMA 2020 guidelines, a comprehensive search was conducted across Scopus, Web of Science, and ERIC databases for peer-reviewed articles published between 2015 and 2025. Twelve studies met the inclusion criteria and passed quality assessment using the Mixed Methods Appraisal Tool. Results reveal a sharp increase in publications post-2020, predominantly from Asian countries (Indonesia, Turkey, Thailand). All included studies reported positive outcomes, with guided inquiry cycles enhanced by reflection, knowledge transfer, and critical thinking components demonstrating significant improvements in students' problem-solving abilities compared to traditional instruction. Thematic analysis identified consistent instructional patterns including student worksheets, real-world problem contexts, and collaborative activities. However, gaps remain in longitudinal research, technology integration, and teacher professional development. This study proposes the Integrated Guided Inquiry–Deeper Learning Framework (IGI-DLF) as a conceptual guide for educators and researchers. The findings conclude that integrating deeper learning principles within inquiry-based approaches effectively fosters higher-order thinking and problem-solving competencies. Future research should focus on long-term skill retention, artificial intelligence scaffolding, and cross-cultural validation to advance mathematics and science education globally.